Binaural Beats as Digital Drugs: Assessing Awareness and Usage Patterns in Nigerian Sports Communities - Olowoleni, Victor Ben; Adegbesan, Olufemi Adegbola; Ayodele, Kolade Babatunde; Okundare, Ayobami Alade; Okanlawon, Ayobami Joseph; Oshadare, Deborah (Universitas Negeri Surabaya, 2026)
Purpose: The emergence of digital drugs (binaural beats) presents a novel and under-researched challenge within sports, particularly in contexts like Nigeria where psychological support structures are often underdeveloped. This study aimed to assess the level of awareness, sources of information, and usage patterns of digital drugs among Nigerian sports personnel (athletes, coaches, medical staff) and to examine the relationship between awareness and indicators of addiction-like behaviour. Materials and Methods: A cross-sectional survey design was employed, with data collected from 297 personnel via a validated questionnaire (α=.89). Data analysis utilized descriptive statistics, Pearson correlation, one-way ANOVA, and chi-square tests. Result: Findings revealed a critical knowledge deficit: only 28.6% of respondents were familiar with the term